CODE-MIXING WITHIN THE USE OF KHEK LANGUAGE ON CHINESE-INDONESIAN ETHNIC IN TAMBORA - Rubica Himawan Evto; Agriska (Universitas Widyatama, 2022)
This research was done with the purpose to provide information and knowledge about code-mixing that used to use in the daily activities of Chinese-Indonesian ethnic in Tambora district, West Jakarta. Although Chinese-Indonesian ethnic had been part of Indonesia, they were still holding their ancestor cultures. One of the cultures was using Chinese language. Sometimes, their spoken were combined between Indonesian language and Chinese language. We tried to analyse that phenomenon which was known as code mixing, in a qualitative method. Our respondents were from the different ward in the Tambora district and the majority of them were from Duri Selatan, Duri Utara, and Tambora. The result of this research showed that there were three major Chinese languages that were frequently used by our respondents. Those three languages are Khek, Hokkien, and Mandarin. We found that the majority of our respondents used Khek language in their communication between family members, from the youngest to the eldest generation. It is only elder generation that most often used code-mixing between Chinese language and Indonesian language in their daily communication.